Hematologic variables of the Arrau turtle (Podocnemis expansa) under the effects of different anticoagulants and cytologic stains - Garcia, Guilherme C (Veterinary clinical pathology, 2021)
© 2021 American Society for Veterinary Clinical Pathology.